AMORPHO BACKER ANEKA ROTI SUWEG SEBAGAI MAKANAN ALTERNATIF PENDERITA DIABETES MELLITUS - Retno Wahyu Wulandari (Inisiasi, 2023)
In this innovation, it contains the manufacture of alternative food made from suweg flour, namely in the form of bread made from the main ingredients specifically for consumption by people with diabetes mellitus. This is because suweg has a low glycemic index (GI) (less than 55) so suweg is safe for consumption for people with diabetes mellitus because it does not accelerate blood sugar levels. Making bread from suweg flour does not only consist of the main ingredient of suweg flour, but suweg flour is still substituted with wheat flour because wheat contains a lot of gluten which is bound to protein as the main requirement in making bread. Making bread from suweg flour is carried out by the following process: mixing suweg flour and wheat flour with a predetermined ratio, adding eggs, salt and water then stirring until the bread dough is smooth. Then, the bread is printed using a bread maker and processed by boiling it first. From the results of the proximate test for the levels of carbohydrates, protein, fat and water, it was found that the average suweg bread had carbohydrate content between 23.44 - 23.98%, protein 4.19% - 5.88%, fat 17.19% - 17.73% and water content 53.88% - 54.45%. Meanwhile, from the results of the taste preference test, the most preferred ingredient composition was 75% suweg flour and 25% wheat flour, for texture and color aroma the most preferred was bread with an ingredient composition of 25% suweg flour and 75% wheat flour.